Experimental and representative watersheds as a training site of qualified professionals in water resources: a case study of Onça Creek Watershed (SP, Brazil) - Alan Reis; Rubens Takeji Aoki Araujo Martins; Luís Eduardo Bertotto; Érick Rúbens Oliveira Cobalchini; Yuri Batista Ishizawa; Edson Cezar Wendland (Revista Brasileira de Recursos Hídricos, 2022)
ABSTRACT This study aims to present how continuous and systematic monitoring in representative and experimental watersheds can help form high-level professionals and researchers in water resources, based on a case study of the Onça Creek Watershed (OCW). Through a historical survey of the monitoring network and the scientific studies carried out in the area, we identified people and map their geographical and professional location, to analyze the impact and importance of this area for the water resources community. We identified 90 scientific studies already developed at the OCW, which resulted in 22 masters and 4 Ph.D. students formed, involving another 33 external collaborators. We observed that 85% of the trained professionals continue to exercise functions related to water resources, in public and private institutions, throughout Brazil and abroad. We highlight the importance of financial support from research and development agencies, both for the monitoring network expansion and the training students' scholarships. We believe that the involvement of water resources graduate programs can be a way to increase the number of experimental and representative watersheds monitored in Brazil.